Three-year Follow-up Results of a Prospective, Multicenter Study in Overactive Bladder Subjects Treated With Sacral Neuromodulation - Siegel, Steven; Noblett, Karen; Mangel, Jeffrey; Griebling, Tomas L.; Sutherland, Suzette E.; Bird, Erin T.; Comiter, Craig; Culkin, Daniel; Bennett, Jason; Zylstra, Samuel; Kan, Fangyu; Thiery, Elizabeth (Urology (Ridgewood, N.J.), 2016)
To evaluate the therapeutic success rate, and changes in quality of life (QOL) and safety in subjects using sacral neuromodulation (InterStim System) at 36 months. Subjects with bothersome symptoms of overactive bladder (OAB) including urinary urge incontinence (UI) and/or urgency frequency (UF), who had failed at least 1 anticholinergic medication, and had at least 1 untried medication were included. Subjects with successful test stimulation received an InterStim implant. Therapeutic success and quality of life through 36 months was evaluated in implanted subjects with data at baseline and follow-up. Safety was evaluated using reported adverse events. A total of 340 subjects received test stimulation resulting in 272 implanted subjects. Demographics include 91% female, mean age of 57 years, and baseline symptom severity of 3.1 ± 2.7 leaks/day (UI) and 12.6 ± 4.5 voids/day (UF). The analysis showed an OAB therapeutic success rate of 83% (95% confidence interval: 78%-88%). UI subjects had a mean reduction from baseline of 2.3 ± 2.3 leaks/day whereas UF subjects had a mean reduction of 5.3 ± 4.0 voids/day (both P < .0001). Statistically significant improvements were observed in all measures of the International Consultation on Incontinence Modular Questionnaire-OABqol (all P < .0001). Eighty percent of subjects reported improvements in their urinary symptom interference. Device-related adverse events occurred in 47% (127/272) of subjects post-implant; 91% were resolved at the time of this analysis. The 36-month follow-up data from the multicenter study demonstrate sustained safety, effectiveness, and improved QOL in subjects implanted with InterStim, without requiring failure of all medications.